Analisis Dampak Kebijakan Alokasi Anggaran Untuk Sektor Pariwisata Terhadap Ekonomi Masyarakat Dan Wisata Keberlanjutan Di Dago Dreampark Bandung Barat - Alfi Dewi Safitri, Nur; Ramdani, Dadan (CV. SINAR HOWUHOWU, 2025)
This study aims to analyze the impact of government budget allocation policies on the tourism sector, particularly in the context of their impact on the local economy and tourism sustainability in the Dago Dreampark area, West Bandung. The research method used was descriptive qualitative with a case study approach, through in-depth interviews with visitors, local business owners, local residents, and tourism managers. The results indicate that the existence and development of Dago Dreampark have had a significant positive impact on the community, particularly economically, such as increased employment and local business opportunities. From a socio-cultural perspective, interactions between tourists and the community encourage the exchange of values and increase social openness, although this requires cultural adaptation. Environmentally, the management of the tourism area is considered quite well-organized in terms of cleanliness, but issues such as congestion and noise remain major challenges, particularly during the holiday season. The study also found that local government budget allocation plays a significant role in supporting tourism development, both through basic infrastructure development and operational funding assistance. However, the technical and operational management of the tourism area is largely carried out independently by the managers, utilizing funds from various sources, including tourist contributions and government assistance. To achieve sustainable tourism goals, a more holistic budget allocation policy is needed, focusing not only on physical development but also on community empowerment, local cultural preservation, and environmental protection. This study concludes that the success of tourism sector development is measured not only by the increase in visitor numbers but also by its impact on the community's quality of life and the sustainability of natural resources.